Assessment of immunization coverage in an urban slum of bangalore city - C Karthik; Shobha; TS Ranganath; P Sushmitha (Asian Pacific Journal of Health Sciences, 2015)
Introduction: Prophylactic primary immunization given in the first year of life against the vaccine preventable diseases (VPD’s) is an effective primary mode of prevention, wherein nearly 2-3 million lives are saved annually[1]. Post-National Immunization Programme era has witnessed a dramatic decrease in the incidence of the VPD’s.Albeit active implementation of the programme, illiteracy, fear, lack of transportation and many other reasons has resulted in drop outs and partial immunization cases. The present paper was conducted to assess the coverage of immunization in the children in an urban slum and to know reasons for being a dropout. Objectives: To estimate the coverage of primary immunization in an urban slum in Bangalore city and to determine the reasons for partial immunization or non-immunization. Methodology: A cross sectional study done among children who have completed one year of age in an urban slum in Bangalore city between the period of August to December 2013.Results: In the study conducted among 210 children 198 (94.3%) were completely immunized and 12 (5.7%) were partially immunized of which 6(50 %) abstained due to AEFI. Lack of faith, myth and contraindications contribute to 8.3% each. Conclusion: The prime reason behind partial immunization as per our study is the fear of AEFI and abstinence due to the same. Time constraints and contraindications were other factors. Immunization status of the child is also seen to be affected by the mother’s literacy status.